Media Literacy and The Prevention of Fake News among Students - Dianah, Lili; Tetep, Tetep (Jurnal Pendidikan Progresif, 2024)
Abstract: Media Literacy and The Prevention of Fake News among Students. Objectives: The spread of hoax news among university students is a problem that needs attention with the increasing use of social media and easy access to information. This study aims to evaluate the extent to which media literacy skills influence media consumption habits, knowledge and awareness, skills and practices, attitudes and beliefs, as well as behavior and engagement in preventing hoax news among students of the Social Science Education IPI Garut. Methods: The research method used is a survey method. The approach taken is a correlational quantitative approach, which allows for measuring the strength of the relationships between these variables. Data were collected by distributing questionnaires online via Google Forms. A sample of 123 active students from the Social Science Education Program at IPI Garut participated as respondents in this study, selected using a proportional stratified random sampling technique. The instrument used was a questionnaire distributed to students online. The data were analyzed using SPSS. Findings: The results of the study show a significant relationship between media literacy skills and the prevention of hoax news among students. Conclusion: It was found that the correlation in media consumption habits at 0.297, which falls into the low category, in knowledge and awareness at 0.510, which falls into the medium category, in skills and practices at 0.523, which falls into the medium category, in attitudes and beliefs at 0.658, which falls into the strong category, and in behavior and engagement at 0.688, which falls into the strong category. Keywords: media literacy, preventing hoax news, students.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202443